Romania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper discusses benefits of boosting quality public infrastructure spending in Romania. Since the financial crisis, fiscal and current account deficits have been tackled, but the infrastructure deficit has widened. Quality public investment in infrastructure can boost domestic demand and potential GDP growth, particularly in low growth environments. The IMF staff simulations employing the European Union's production function methodology show significant growth benefits from higher quality infrastructure spending. As a result of higher investment, real GDP would increase by about 1 percent initially with the impact peaking in 2025.